Effect of SiO2-doping on photogenerated cathodic protection of nano-TiO2 films on 304 stainless steel. (15th July 2017) - Cheng, Wenhua; Li, Chundong; Ma, Xiao; Yu, Liangmin; Liu, Guangyi
Abstract: In this study, SiO2 -TiO2 composite films were prepared on 304 stainless steel (SS) by a sol-gel method and dip-coating technology. The impact of doping SiO2 on the microstructure and photoelectrochemical performance of the films was investigated. The results demonstrated that pure TiO2 film was composed of anatase and rutile. Doping the film with SiO2 suppressed the phase transformation of anatase to rutile and decreased particle sizes of the films. SiO2 also reduced fluorescence intensity of the composite films, inhibiting the recombination of electrons and holes. Optical absorption intensity of the films first increased and then decreased with increasing SiO2 . The corrosion potential of the coated 304SS in 3.5% NaCl in the dark increased along with SiO2 content. Under illumination, however, the 304SS with 10% SiO2 -TiO2 film behaved the lowest corrosion potential and smallest charge transfer resistance. Further SiO2 addition caused an amorphous film and suppressed light absorption, resulting in decreased photoelectrochemical performance. Graphical abstract: Highlights: SiO2 doping into TiO2 film suppressed the phase transformation of anatase to rutile and decreased particle sizes. Anti-corrosion ability of SiO2 -TiO2 -coated 304 stainless steels in 3.5% NaCl in the dark increased along with SiO2 content. Photogenerated cathodic property of coated 304SS first increased and then decreased under UV light with increasing SiO2 . Additional SiO2 caused anatase disappear and an amorphous insulator film, deceasing photoelectrochemical property of coated 304SS.